1999
DOI: 10.1046/j.1525-1470.1999.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Lupus Panniculitis and Antiphospholipid Syndrome in a Patient Without Complement Deficiency

Abstract: Generalized chronic cutaneous lupus including lupus panniculitis in childhood is rare and usually occurs in the setting of genetic complement deficiencies. The association with antiphospholipid syndrome is even more rare. We report a 13-year-old girl with extensive lupus panniculitis since the age of 8 months and no evidence of complement deficiency. She recently developed antiphospholipid syndrome characterized by anticardiolipin antibodies and digital necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Skin manifestations of antiphospholipid antibody syndrome in children reportedly include a high incidence of livedo reticularis and digital ischemia. 13,14 However, our patient did not develop these features throughout the observation period.…”
Section: Anticardiolipin Antibodies In Infancycontrasting
confidence: 52%
“…Skin manifestations of antiphospholipid antibody syndrome in children reportedly include a high incidence of livedo reticularis and digital ischemia. 13,14 However, our patient did not develop these features throughout the observation period.…”
Section: Anticardiolipin Antibodies In Infancycontrasting
confidence: 52%
“… 134–139 A recent study indicates a relatively low frequency of association with SLE and a paucity of serologic abnormalities typically associated with a connective tissue disease diathesis; 140 50% of patients had no other clinical features of LE. 140 Pediatric patients with antiphospholipid antibody syndrome and/or hereditary complement deficiency 141 may present with LEP. Lupus erythematosus profundus affects approximately 1 to 2% of patients with LE.…”
mentioning
confidence: 99%
“…It occurs primarily in middle‐aged (40 to 50 years old) women and has a predilection for the buttock, arms, thighs and face (7). It is rare in children (3, 4). Clinically, lupus panniculitis is usually characterized by the appearance of persistent, firm, well‐defined nodules or plaques which are rarely as extensive as the involvement seen in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized forms of lupus panniculitis have been associated with hereditary complement deficiencies, particularly of C2 and C4 (8). Nousari et al (4) reported that excluding a case of lupus panniculitis associated with neonatal lupus and a case of pancreatic panniculitis in a patient with lupus erythematosus, only four cases of generalized lupus panniculitis have been reported in children under the age of 13. Our patient showed severe, extensive, deforming lupus panniculitis with no evidence of genetic complement deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation